Exploring the User’s View on Design Patterns for Technology-Enhanced Learning - Derntl, Michael; Motschnig-Pitrik, Renate (Proceedings of the International Conference on Networked Learning, 2008)
The use of design patterns for creating technology-enhanced learning (TEL) environments has gained significant momentum in recent years. In the TEL community the concept of patterns was introduced and spread by various pattern initiatives and projects. Patterns are meanwhile a widely familiar concept for both researchers and practitioners. Essentially, a pattern gives a description of a reusable solution to a common design problem in some context. In the context of TEL and in pedagogy, patterns are typically used to describe effective teaching methods, situations or teaching/learning activities. Even with a significant number of e-learning and TEL design patterns available today, there is still only little evidence of actual usage and usability of that knowledge base in the TEL domain. The past focus has been on introducing patterns to the field and creating patterns from existing design and application experience. But any innovation needs to show its qualities and benefits to the users if it is intended to succeed; patterns without users working with them are, literally, useless artefacts. Therefore, in this paper, we aim to provide a thorough exploration of the user’s view on design patterns for TEL. We intend to investigate qualities and features of patterns and pattern collections which we consider essential for raising the usability of patterns. Thereby we consulted several sources on pattern qualities, requirements, life cycle and use cases as found in the original pattern work by Alexander as well as in more recent literature. On the other hand, we draw from own experience and research during several years of finding, writing and applying patterns in higher-education TEL settings. To enable continuing research and improvement based on findings, insights and lessons learned during TEL pattern application, we propose a cyclic model of the pattern application process; we investigate the application of design patterns along the five phases of Action Research: diagnosing, action planning, action taking, evaluating, and specifying learning. This cyclic phase arrangement seems particularly suited for pattern application, as we believe that the quality of patterns and the success of their application heavily rely on the user’s ability to integrate lessons learned and experiences drawn into future application cycles. In the core part of the paper we use the cyclic process of design pattern application for definition and analysis of critical factors of the user’s perspective for each phase as well as input and output elements of each phase. In a nutshell, the phases of the application cycle and their relation to pattern features from the user’s viewpoint are characterized as follows. The diagnosing phase includes understanding the application context, finding appropriate patterns and understanding the patterns. This is supported by building a pattern repository upon some clearly expressed value base or philosophy. Also, patterns need to be structured to guide users in finding and selecting appropriate patterns for their design problems. To be understandable, patterns need to convey their advice in an efficient, generative way. For action planning and action taking patterns should, particularly in the TEL domain, include details on required technology support, essential actions and critical success factors to be considered, as well as pitfalls known from previous applications. To be amenable to evaluation, patterns need to clearly express their intent and expected effects, and include evidence on their effectiveness; to collect evidence each pattern can, for instance, provide guidance on collecting empirical data. The pattern user also has a responsible role in pattern evolution through feeding back his/her insights and experience during pattern application. We should strive to exploit network effects by sharing advice, feedback, and experience through design patterns. In the paper, we ‘walk through’ the phases of the proposed application cycle based on an example case in the context of involving students in the evaluation of their learning at the end of a concrete course. We conclude that continuous information flow and cooperation between pattern designers and users are essential in equipping patterns with the features needed to facilitate their finding, selection, application, organization and evolution.